Pelatihan Pembuatan Modul Ajar Interaktif dengan Powerpoint VBA pada Guru SMK Nahdlotul Ulama - Didin Herlinudinkhaji; Lingga Kurnia Ramadhani; Nindita Erwanti; Yunila Putri Dwi Ariyanti (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
Online learning is a necessity so that in the process of online learning, schools and teachers must be able to adjust to these developments. Schools are required to be more effective in organizing learning while teachers are required to be more creative in delivering learning material. In the process of teaching and learning online, there are many complaints from students and teachers. The training activities for making teaching modules with MS Powerpoint is expected to role in the teaching and learning process which is carried out online because of the limitations of teachers in direct interaction with students. In this activity using direct practice methods with guidance from the PKM team. The results show that before participating in the training, teachers have not been able to make interactive teaching modules. After receiving training, teachers already understand the importance of interactive teaching modules.